CLINICAL AND MORPHOLOGYCAL DESCRIPTION OF RECTAL CANCER - Yakimova, T.P.; Svynarenko, A.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The data about histological varieties and proliferation activity of rectal adenocarcinomas evaluated in biopsies taken from untreated patients with resectable rectal cancer are presented.